2018
DOI: 10.1088/1361-6471/aaa2bf
|View full text |Cite
|
Sign up to set email alerts
|

Nucleon transfer reactions with radioactive beams

Abstract: Transfer reactions are a valuable tool to study the single-particle structure of nuclei. At radioactive beam facilities transfer reactions have to be performed in inverse kinematics. This creates a number of experimental challenges, but it also has some advantages over normal kinematics measurements. An overview of the experimental and theoretical methods for transfer reactions, especially with radioactive beams, is presented. Recent experimental results and highlights on shell evolution in exotic nuclei are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 172 publications
3
44
0
Order By: Relevance
“…Transfer reactions provide an efficient tool to study the single-particle structure of nuclei away from stability [3][4][5][6][7][8]. They are therefore used to study halo structures, like in 11 We have reanalyzed these data within the ADWA model of transfer [16], using a Halo-EFT description of 11 Be at leading order [27,28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transfer reactions provide an efficient tool to study the single-particle structure of nuclei away from stability [3][4][5][6][7][8]. They are therefore used to study halo structures, like in 11 We have reanalyzed these data within the ADWA model of transfer [16], using a Halo-EFT description of 11 Be at leading order [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally, the upgrade of rare isotope beam facilities worldwide provides us with many ways to explore these halo systems. Transfer reaction [3][4][5][6][7][8] has been an important tool to infer information about these systems for decades. In this reaction, one or several nucleons are transferred between the projectile and target.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent reviews can be found in Refs. [158,159]. An important feature of these reactions is that the angular distributions of the outgoing particles reflects the transferred orbital angular momentum with respect to the "core" or residual.…”
Section: 1 Transfer Reactionsmentioning
confidence: 99%
“…Note that as only the modulus squared of the two S-matrices are needed for the stripping component [Eq. (159)], then only the imaginary part of the eikonal phase, and hence, the imaginary optical potentials are needed. However the real parts are needed for the diffractive part, but this component is typically much smaller [191].…”
Section: Heavy-ion Knockout Reactionsmentioning
confidence: 99%